Post Partum Depression among Women Attending Maternal and Child Health Clinic in Selected Hospitals of Nepal - Mishra, Durga; Shakya, Dhanedra Veer; Pathak, Ram Sharan; Mishra, Smriti (Journal of Manmohan Memorial Institute of Health Sciences, 2019)
Background: The postpartum non-psychotic depression is one of the most common complications of childbearing affecting about 10-15 % of women and is representative prevalence to consider as a public health problem affecting women and their families. The major objectives of this study were to assess magnitude of postpartum depression and to identify possible reasons. Methods:Mixed method was adopted for the study. Individual interview questionnaire andNepali version Edinburgh Postnatal Depression Scale (EPDS) were used as quantitative tool among 260 women attending MCH clinic for vaccinating their children under the age of one from purposively selected three Tarai hospitals in Nepal. 248 respondents were included in the analysis. For the qualitative part, Focus Group Discussion (FGD), In-depth interview (IDI) and Key Informants Interview (KII) were used. Data analysis was done usingSPSS (20). Chi-square test was done to show strength of association. Theme building was done for qualitative analysis. Findings from both studies have been triangulated. Results: Among the 248 respondents 177 (71.4%) of them showed no signs of depression however, in the 71 (28.6%) respondents the postpartum depressionwas found through EPDS. The prevalence of postpartum depression was seen in all kinds of socio- economic and demographic characteristics but varied in the magnitude. Conclusions: Women from anywhere can be sufferers of the post partum depression and the findings of this study would be an important evidence for an individual, family, community and policy makers and programme designers/implementers in managing this problem properly.